Dynamics Characteristic Analysis of Sliding Bearing-rigid Rotor System with Flexible Support - Wenbin Wang (Jixie chuandong)
Considering the influence of nonlinear factors such as oil film force support of sliding bearing and external excitation of flexible support， a rigid rotor model with flexible supports at both ends is established. The dynamics behavior of the system is numerically simulated by using the fourth-order variable step size Runge-Kutta algorithm， the displacement bifurcation diagrams of the rigid rotor system varying with rotational speed with different external excitation amplitudes，and the phase diagram and Poincaré map under specific parameters are obtained. These diagrams directly reveal the dynamic characteristics of the system. The results show that the complex dynamic behaviors such as chaos， multi period，almost periodic and single period appear with the increase of rotating speed in the middle and low speed stage， in the middle speed and high speed stage，the system is mainly the mutual transfer of multi period and chaotic motion，and the emergence of paroxysmal chaotic motion. With the increase of the amplitude of external excitation， the system is easy to form almost periodic motion， and the oil film force at the journal bearing bush increases.